Operator, organizational, and field maintenance manual : voltmeter, phase angle ME-223/U and North Atlantic Industries models 202R and 202AR. - United States. Department of the Army ([Washington, D.C.] : Headquarters, Dept. of the Army, 1989)
"August 1962." Shipping list no.: 89-735-P. Cover title. Includes bibliographical references (p. 3 (1st group)). Mode of access: Internet. 14